2017
DOI: 10.1007/s10120-017-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of FGFR2 mRNA and comparison with FGFR2 gene copy number by dual-color in situ hybridization in a large cohort of gastric cancer patients

Abstract: BackgroundFibroblast growth factor receptor (FGFR2) has been proposed as a target in gastric cancer. However, appropriate methods to select patients for anti-FGFR2 therapies have not yet been established.MethodsWe used in situ techniques to investigate FGFR2 mRNA expression and gene amplification in a large cohort of 1036 Japanese gastric cancer patients. FGFR2 mRNA expression was determined by RNAscope. FGFR2 gene amplification was determined by dual-color in situ hybridization (DISH).ResultsWe successfully a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Gene amplification is a common cause for mRNA overexpression. In fact, a recent in situ analysis showed that FGFR2 mRNA is highly correlated with FGFR2 amplification in primary cases clinically, where a high expression level of FGFR2 is associated with poor survival rate of GC patients [76]. Recently, FGFR2 overexpression has been detected in a great portion of GC cases by immunohistochemistry staining, the high level FGFR2-IIIb isoform predicts poor overall survival in patients [19].…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…Gene amplification is a common cause for mRNA overexpression. In fact, a recent in situ analysis showed that FGFR2 mRNA is highly correlated with FGFR2 amplification in primary cases clinically, where a high expression level of FGFR2 is associated with poor survival rate of GC patients [76]. Recently, FGFR2 overexpression has been detected in a great portion of GC cases by immunohistochemistry staining, the high level FGFR2-IIIb isoform predicts poor overall survival in patients [19].…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…The amplified FGFR2 induces the activation of FGFR2 signaling. FGFR2 has been proposed as a target for targeted therapy of GC (Pearson et al, 2016;Kuboki et al, 2018;Kim et al, 2019). Yu et al (2018) revealed that overexpressed FGFR2 accelerated the production of cancer-initiating cells (CIC) and enhanced the resistance to lapatinib in HER2-positive GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation criteria for each immunohistochemical markers and RISH was described in Table S2. Evaluation criteria were referred from previous studies investigating each molecule [37][38][39][40].…”
Section: Evaluation Of Ihc and Rishmentioning
confidence: 99%